2010
DOI: 10.1111/j.1742-481x.2010.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic platelet gel in the treatment of pressure sores: a pilot study

Abstract: Although platelet gel is considered one of the most popular tools in the treatment of chronic ulcers, current consensus on its use is not unanimous. A prospective randomised trial was carried out at the Plastic Surgery Unit of the 'Salvatore Maugeri' Foundation Hospital of Pavia (Italy). The study involved 13 patients affected by spinal cord injury with 16 pressure sores over a period of 20 months. The ulcer was considered the experimental unit of the study irrespective of the number of ulcers per patient. Eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 22 publications
2
28
0
2
Order By: Relevance
“…The present study corroborates the findings of the Rappl 5 who reported that most healing occurred in first 3-4 weeks of treatment, and also of Scevola et al 14 who reported that in subjects with SCI and deep PrUs , there was a statistically significant increase in the onset of the granulation phase of wound healing, the healing process was triggered faster and there was more healing in the first 2 weeks of treatment with allogenic PRP gel compared with 'current best-practice approach to chronic wound-dressing protocol' . It is generally accepted that platelet growth factors have a central role in the healing process and tissue formation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study corroborates the findings of the Rappl 5 who reported that most healing occurred in first 3-4 weeks of treatment, and also of Scevola et al 14 who reported that in subjects with SCI and deep PrUs , there was a statistically significant increase in the onset of the granulation phase of wound healing, the healing process was triggered faster and there was more healing in the first 2 weeks of treatment with allogenic PRP gel compared with 'current best-practice approach to chronic wound-dressing protocol' . It is generally accepted that platelet growth factors have a central role in the healing process and tissue formation.…”
Section: Discussionsupporting
confidence: 93%
“…3,5,[10][11][12][13][17][18][19] Only very few studies have evaluated its role in PrUs in the SCI population. 3,5,10,11,14 The purpose of the present prospective study was to evaluate the application of PRP in relation to PrUs healing on the basis of clinical, wound size measurement and histopathological features versus saline dressing on the other PrU in the same patient. There was statistically significant decrease in mean PUSH scores of PrUs (case) (t ¼ 6.13, Po0.000) and PrUs (control) (t ¼ 3.98, P ¼ 0.000) after 5 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the use of pooled blood is typically frowned upon in the United States, the use of allogenic PRP has been gaining popularity in a number of European studies with no mention of adverse immune reactions. [53][54][55][56] FIG. 12.…”
Section: 51mentioning
confidence: 99%
“…12 Otolog trombosit jel, yüksek miktarda büyüme faktörlerini içerdiğinden doku onarımı ve rejenerasyonunda belirgin bir hızlanma sağlamaktadır. 29 Eritropoietin mitozu stimüle edip, anjiyogenezi uyarır ve hemoglobin düzeyi-ni arttırarak doku oksijenizasyonunu arttırır. Böylece bası yarasının iyileşmesini hızlandırmaktadır.…”
Section: Yeni Tedavi Yöntemleriunclassified